1982
DOI: 10.1104/pp.69.4.911
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Respiration of Developing Populus tremuloides Internodes

Abstract: The photosynthetic and respiratory performance of developing internodes of Popudus tremuloides was evaluated by infrared gas analysis.Anatomical and morphological transitions were related to metabolic activity. Photosynthetic rates ranged from 6.0 to 10.0 milligrams CO2 per decimeter squared per hour in the youngest internodes to 2.5 to 3.8 milligrams CO2 per decimeter squared per hour in internodes with fully developed bark tissues. Respiration exceeded the rate of photosynthesis on the average by a factor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In young twigs of beech with 80-90% respiration reduction, an even higher carbon re-fIxation activity was found. These data are in agreement with those of Foote and Schaedle (1 976a,b) and Brayman and Schaedle (1982).…”
Section: C) Contributions Of Corticular Photosynthesis To the Carbon supporting
confidence: 94%
“…In young twigs of beech with 80-90% respiration reduction, an even higher carbon re-fIxation activity was found. These data are in agreement with those of Foote and Schaedle (1 976a,b) and Brayman and Schaedle (1982).…”
Section: C) Contributions Of Corticular Photosynthesis To the Carbon supporting
confidence: 94%
“…(trembling aspen), a broad-leaved, deciduous angiosperm. The capacity of P. tremuloides bark for photosynthetic refixation is well documented (Pearson and Lawrence 1958;Strain and Johnson 1963;Schaedle 1976, 1978;Brayman and Schaedle 1982;Schaedle and Brayman 1986;Kharouk et al 1995). Photosynthetic refixation approaching 80% of dark respiration was recently reported in Pinus monticola branches (Cernusak and Marshall 2000).…”
Section: Plant Materialsmentioning
confidence: 96%
“…In P. tremuloides refixation rates ranged from 3.8-6.3 µmol CO 2 m -2 s -1 in the youngest internodes to 1.6-2.4 µmol CO 2 m -2 s -1 in the older ones; corresponding dark respiratory rates were between 18.3 and 4.4 µmol CO 2 m -2 s -1 (Brayman and Schaedle 1982). While Foote and Schaedle (1978) described aspen bark photosynthesis about 5.7-7.6 µmol CO 2 m -2 s -1 , Kharouk et al (1995) reported slightly higher values between 8 and 10 µmol CO 2 m -2 s -1 .…”
Section: Gas Exchange Of Twigs and Leavesmentioning
confidence: 98%
“…Nowadays, photosynthesis in woody stems is best known in the greenish cortex of P. tremuloides, but positive net CO 2 assimilation by illuminated aspen bark has never been reported (e.g. Pearson and Lawrence 1958;Strain and Johnson 1963;Schaedle 1976a, b, 1978;Brayman and Schaedle 1982;Cernusak et al 2001). Nevertheless, aspen bark photosynthesis represents an efficient mechanism for the stem-internal re-assimilation of respiratory carbon dioxide, probably contributing to the broad ecological amplitude of trembling aspen (e.g.…”
Section: Introductionmentioning
confidence: 98%